Perancangan Sistem Informasi Simpan Pinjam Koperasi (Studi Kasus Pada Koperasi Simpan Pinjam Soliamitra) - Ela Nurelasari - AMIK BSI Jakarta (Universitas Bina Sarana Informatika, 2016)
ABSTRACT - Cooperative Soliamitra is one institution that is located in the Village business district Limo Limo Depok, Starting from a casual chat group of volleyball players